BRIDGING SKILL GAPS THROUGH COMPETENCY MAPPING: AN ANALYSIS OF OUTPUT MANAGEMENT IN NAGPUR’S SMALL-SCALE MANUFACTURING SECTOR - Siddiqui, Aftab Ali; Waiker, Vinod (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present research paper aims at explaining the role of competency mapping in the process of capability enhancement and its contributions on output management of small scale manufacturing industries in Nagpur region. In an environment characterised by stiff competition, there is nothing as vital as ensuring that the skills acquired by the employees are well fit for the need of the organisation as far as productivity is concerned. The purpose of this paper lies in analysing the efficiency of competency frameworks regarding the identification of skills shortage, development of workforce resources, and increase of the organisational productivity. A cross-sectional survey of employees fills the quantitative gap in measuring the competencies and the organisational output of the companies, and interviews with the HR professionals and experts provides a qualitative component to effectively capture the research questions and the issues regarding the competency mapping system in organisations. It reveals that although small-scale manufacturers in Nagpur appreciated the competency mapping concept, many of them including a range of barriers like inadequate resource and irregular training. In other words, the study provides evidence that the key to skill deficits can be effectively addressed through competency development by enhancing output performance, identifying performance enhancement strategies of existing and potential employees, and managing change processes to support marketplace requirements. The paper contains the specific advice which will help small-scale industries improve the competency mapping approaches and use them for the organizations’ long-term development.